Can Ischemia Modified Albumin (IMA) Levels Be a Predictor of Acute Pancreatitis? - Yarkıcı, Hakan; Derviş Hakim, Gözde; Arı, Elif Merve; Akar, Harun; Çolak, Ayfer (Turkish Journal of Gastroenterology, 2021)
Background: We aimed to evaluate the value of ischemia modified albumin (IMA) as a prognostic marker in acute pancreatitis (AP) patients, determine whether it is efficient in assessing the disease severity or not, and to estimate the correlation between IMA and the inflammatory markers, prognostic markers and scoring systems routinely used in clinical practice. Methods: 100 adult patients (18 years and older) who have been hospitalized and evaluated with AP diagnosis in Tepecik Training and Research Hospital, Department of Gastroenterology, between April 1, 2017 and April 1, 2018 have been enrolled in the study. Patients have been stratified disease etiology (biliary or non-biliary). The non-biliary group has been divided into subgroups as alcoholic, lipemic, or idiopathic. Disease severity has been categorized as mild, moderate, or severe pancreatitis according to the Atlanta classification. Ranson, Harmless Acute Pancreatitis Score (HAPS), Bedside Severity Index for Acute Pancreatitis (BISAP) scores have been determined for each patient. Patients have been grouped as necrotizing or edematous according to the Atlanta classification. Results: According to our findings, IMA has been found to be correlated with disease severity, Ranson and BISAP scores, and procalcitonin levels. We have observed that some laboratory parameters including blood urea nitrogen and hematocrit levels and HAPS scoring system are not correlated to IMA. Conclusion: Our study is the first study to compare multiple prognostic factors with IMA in AP patients. In our study, the association between IMA and AP has been evaluated in the context of prognostic scoring and disease severity.